Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik pada Materi Sistem Pencernaan Manusia di Kelas XI SMA Negeri 1 Moutong - Malasugi, Regina R.; Mamu, Hartono D.; Jannah, Magfirahtul; Lamondo, Djuna; Yusuf, Frida Maryati (Biocaster : Jurnal Kajian Biologi, 2025)
This study aims to determine the effectiveness of the application of the Problem Based Learning model to improve students' critical thinking skills on the human digestive system material of class XI of SMA Negeri 1 Moutong. The study used a pre-experimental design method with a one group pretest-posttest design approach involving 25 students of class XI IPA2. The research instruments included critical thinking tests (pretest and posttest), learning implementation sheets, student activity sheets, and student response questionnaires. The results showed that the learning implementation reached an average of 94% with the category (very good), student activity 94% (very good), and student response 91% (very positive). The average pretest score of 42.2 increased to 79.2 in the posttest with an N-Gain value of 0.59 (moderate category). Significant improvements occurred in the indicators of providing simple explanations and organizing strategies or actions, increasing from 34.4% and 32% to 92%, respectively. These results indicate that the implementation of the PBL model is effective in improving students' critical thinking skills in the human digestive system.